Chlamydia pecorum–Induced Arthritis in Experimentally and Naturally Infected Sheep. Issue 2 (March 2021) - Ostfeld, Nina; Islam, Mominul M.; Jelocnik, Martina; Hilbe, Monika; Sydler, Titus; Hartnack, Sonja; Jacobson, Caroline; Clune, Tom; Marsh, Ian; Sales, Narelle; Polkinghorne, Adam; Borel, Nicole
Chlamydia pecorum is an obligate intracellular pathogen with a wide host range including livestock such as sheep, cattle, goats, and pigs as well as wildlife species such as koalas. Chlamydial polyarthritis is an economically important disease resulting in swollen joints, lameness, stiffness, and weight loss in young sheep. In the present study, tissues from sheep experimentally or naturally infected with Chlamydia pecorum were assessed by histopathology and immunohistochemistry. Carpal, hock, and stifle joints as well as spleen, liver, kidney, lymph nodes, lung, and brain of 35 sheep from different inoculation groups were available. Two different C. pecorum strains (IPA and E58), different routes of administration (intraarticular or intravenous), UVA-irradiated IPA strain, and corresponding noninfected control groups were investigated. Similar investigations on tissues from 5 naturally infected sheep were performed. The most obvious inflammatory lesions were observed in synovial tissues and, notably, in the renal pelvis from the experimentally infected group and naturally infected animals. This resulted in chronic or chronic-active arthritis and pyelitis. Intralesional chlamydial inclusions could be demonstrated by immunohistochemistry in both tissues. Immunohistochemical evaluation of the presence and distribution of macrophages, T and B cells in synovial tissues revealed macrophages as the most prevalent inflammatory cell population. Previous observations indicated that C. pecorum isolates can infect circulating monocytes. Together with the finding of the histological lesions in synovial tissues and internal organs alongside the presence of C. pecorum DNA, these observations suggest chlamydial arthritis in lambs is the result of hematogeneous spread of C. pecorum .